Asthma is Different in Women - Zein, Joe G.; Erzurum, Serpil C. (Current allergy and asthma reports, 2015)
ABSTRACT Gender differences in asthma incidence, prevalence and severity have been reported worldwide. After puberty, asthma becomes more prevalent and severe in women, and is highest in women with early menarche or with multiple gestations, suggesting a role for sex hormones in asthma genesis. However, the impact of sex hormones on the pathophysiology of asthma is confounded by and difficult to differentiate from age, obesity, atopy, and other gender associated environmental exposures. There are also gender discrepancies in the perception of asthma symptoms. Understanding gender differences in asthma is important to provide effective education and personalized management plans for asthmatics across the lifecourse.